2019
DOI: 10.3389/fpsyt.2019.00051
|View full text |Cite
|
Sign up to set email alerts
|

Association Between 5-HTTLPR Polymorphism and the Risk of Autism: A Meta-Analysis Based on Case-Control Studies

Abstract: Background: Recently, many case-control studies have reported the association between 5-HTTLPR polymorphism and autism risk. However, the results are inconclusive and conflicting. To investigate the genetic association of 5-HTTLPR polymorphism and autism risk, we conducted a comprehensive meta-analysis based on previous case-control studies. Methods: Literature search was performed through PubMed, Embase, Web of Knowledge and CNKI databases until June 27, 2018. The strength o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Replication of results across ethnicities has been postulated as a good strategy to discover true risk variants or to understand if the lack of replication reflects the complexity in the genetic architecture of some complex disorders as ASD [ 64 , 65 ]. Although two meta-analyses recovering case-control studies mainly from European, American, and Asian population did not find association of this polymorphism with ASD, they also confirmed high heterogeneity in the included studies probably explained by population ethnicity [ 27 , 28 ]. These results suggest that the 5-HTTLPR polymorphism varies across ethnicities and the genetic background of each population may have a role in the risk conferred by this polymorphism [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Replication of results across ethnicities has been postulated as a good strategy to discover true risk variants or to understand if the lack of replication reflects the complexity in the genetic architecture of some complex disorders as ASD [ 64 , 65 ]. Although two meta-analyses recovering case-control studies mainly from European, American, and Asian population did not find association of this polymorphism with ASD, they also confirmed high heterogeneity in the included studies probably explained by population ethnicity [ 27 , 28 ]. These results suggest that the 5-HTTLPR polymorphism varies across ethnicities and the genetic background of each population may have a role in the risk conferred by this polymorphism [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 95%
“…The role of 5-HTTLPR polymorphism in the ASD pathophysiology evaluated through casecontrol studies and family-based association have reflected conflicting results. For instance, two studies suggested S allele as risk variant for ASD [15,16], while three meta-analysis did not find association [26][27][28]. We assessed this polymorphism through a case-control approach failing to find association between 5-HTTLPR and idiopathic ASD, and also through a familybased assessment that did not find a preferential transmission of either S or L allele.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…[ 16 19 ] Various meta-analyses on this region also failed to identify any correlations to ASD. [ 20 22 ] Apart from the L and S alleles, there is an A/G single nucleotide polymorphism in 5-HTTLPR named rs25531 which is a functional polymorphism. Two earlier studies reported that 5-HTTLPR with the L allele and A single nucleotide polymorphism on rs25531 (LA haplotype) had higher expression compared to other haplotypes, [ 23 , 24 ] which could affect serotonin levels.…”
Section: Introductionmentioning
confidence: 99%